Novel NPY2R agonist BI 1820237 provides synergistic anti-obesity efficacy when combined with the GCGR/GLP-1R dual agonist survodutide - Robert Augustin; Anouk Oldenburger; Tamara Baader-Pagler; Tina Zimmermann; Jens Borghardt; Jacob Hecksher-Sørensen; Angela Baljuls; Wolfgang Reindl; Bartlomiej Krawczyk; Eric Martel; Albert Brennauer; Stefan Peters; et al. (Molecular Metabolism)
Summary: Objective: Nutrient-stimulated gut hormone peptide YY3–36 (PYY3–36) selectively activates the neuropeptide Y2 receptor (NPY2R) and reduces energy intake in humans. We describe the discovery and pharmacology of the long-acting NPY2R agonist BI 1820237 and its potential bodyweight-lowering efficacy alone and in combination with the glucagon receptor (GCGR)/glucagon-like peptide-1 receptor (GLP-1R) dual agonist survodutide. Methods & Results: BI 1820237 dose-dependently reduced food intake and gastric emptying in lean mice. Significant bodyweight reductions were not observed with BI 1820237 alone in diet-induced obese mice, however combination with survodutide led to bodyweight reduction of 22% which was significantly (p < 0.01) greater than the 17% bodyweight reduction with survodutide alone. Regression-based interaction analysis demonstrated that BI 1820237 increased the efficacy of survodutide by 265% at an ED50 of 11.7 nmol/kg over a range of dose combinations. Conclusion: Synergistic NPY2R and GCGR/GLP-1R agonism provides an attractive mode of action for clinically relevant weight loss in patients with obesity.